Fine tuning of metal-specific activity in the Mn-like group of cambialistic superoxide dismutases. Issue 107 (15th October 2015) - Russo Krauss, Irene; Merlino, Antonello; Pica, Andrea; Rullo, Rosario; Bertoni, Alessandra; Capasso, Alessandra; Amato, Massimo; Riccitiello, Francesco; De Vendittis, Emmanuele; Sica, Filomena
Abstract : Metal-dependent activity and X-ray structures of superoxide dismutase (SOD) from Streptococcus mutans and Streptococcus thermophilus suggest that they are members of the Mn-like group of cambialistic SODs. Abstract : Among Fe/Mn superoxide dismutases (SODs) a very peculiar sub-class is that of cambialistic SODs. These proteins are active with either Fe or Mn in the active site, in contrast with the other SODs that are strictly metal-specific. Here we report the metal-dependent regulation of the activity and the crystallographic structure of the cambialistic SODs from the dental pathogen Streptococcus mutans (SmSOD) and the food-industry bacterium Streptococcus thermophilus (StSOD). The two enzymes share a high sequence identity (86.2%) and present very similar three-dimensional structures. A detailed comparison with the other cambialistic SODs, found in the Protein Data Bank, allowed the identification of two sub-groups of cambialistic enzymes, the Fe-like and the Mn-like. In particular, SmSOD and StSOD were classified as belonging to the Mn-like sub-group; this assignment was in good agreement with the activity data, showing a significantly higher catalysis in Mn-bound forms of SmSOD and StSOD with respect to their Fe-forms. However, in spite of a very similar Mn-dependent activity, SmSOD and StSOD display a consistently different Fe-dependent activity, SmSOD being three-times less efficient than StSOD in the Fe-bound form. The analysis of the X-ray structures suggests that this difference could be related to the effect of a fraction of enzyme molecules possessing an atypical hexa-coordinated iron ion in the active site of SmSOD. These new structural data provide deeper insights into the family of cambialistic SODs.